Maritime Education and the Training Challenges under Applicable Nigeria Laws: Need to Harmonise with Global Best Practices (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
Maritime education and seafarers’ training are crucial to achieving cabotage and maritime law policies. Cabotage law, by its nature as a local content law, presupposes that local nationals are well trained in line with the Standards of Training, Certification and Watchkeeping for Seafarers (STCW) to match the standards of expatriates or foreign counterparts. The need for citizens to be equally qualified in professional terms to man vessels and drive the cabotage industry of their respective countries cannot be overemphasised. Recognising this, Nigeria institutionalised technical training through various regulatory bodies, such as the Nigerian Maritime Administration and Safety Agency (NIMASA) and the National Board for Technical Education (NBTE), to ensure adequate manpower supply in the industry. The study adopted the doctrinal approach to legal research and made use of both primary and secondary sources of law. However, the paper found that Nigeria is confronted with foreign dominance, lack of adequate resources, and financial misappropriation, among other issues. Consequently, as a way forward to achieving the enormous benefits in the industry, access to funding and resources, alongside the fight against corruption, are ways to overhaul the system. Others include staff development, international collaboration, and investment in modern infrastructure and technology. The recommendations are geared towards safeguarding the training and regulatory institutions from collapse and upholding institutional integrity. Nigeria can also adopt the aggressive models of the Philippine system to improve the Nigerian cabotage industry. The findings may also benefit other countries facing similar challenges.